Pengaruh Penerapan Elearning Berbasis Schoology Terhadap Peningkatan Hasil Belajar Siswa (Studi Kasus SMK Negeri 1 Kabanjahe) - Pinem, Sanjaya; Hutagaol, Viktor Edison (LPPM UNIKA Santo Thomas Medan, 2020)
Problems during the learning process at SMK Negeri 1 Kabanjahe are students are less attentive and lack understanding in understanding computer subject, especially building LAN networks. Computer Subject is considered one of the most difficult materials to learn, however multimedia major that they choose should use a computer. therefore, relies on the problem, this research aims to improve the students learning outcome, students’ activities during use schoology, and responses of students when using schoology as an elearning method. Type of this research is Classroom Action Research and the subject of this research is students class X Multimedia SMK Negeri 1 Kabanjahe with 26 students as participants. For collecting data this research use observations of student activities, evaluation tests and questionnaires to student. Result shown that students' learning outcomes improved, as shown from percentage students who completed KKM (minimum competence) in first cycle by 30.80% increased to 85% in the second cycle. the percentage of activity in the first cycle by 51.44% increased to 73.08% in the second cycle and the response of the learners in the poll gave a positive response the average percentage was 77.18% and the negative response percentage was 22.82%